given , f(x)=2*(f(x-1)+g(x-1)-1)*(f(x-1)+g(x-1)-3)+12*f(x-1)-13 g(x)=(f(x-1)+g(x-1))*(f(x-1)+g(x-1)-4)+12*g(x-1)-7 here , f(0)=2,g(0)=1. if x is given how to find f(x) and g(x) when 1<=x<=10^18 and x is an non negative integer
# | User | Rating |
---|---|---|
1 | tourist | 3856 |
2 | jiangly | 3747 |
3 | orzdevinwang | 3706 |
4 | jqdai0815 | 3682 |
5 | ksun48 | 3591 |
6 | gamegame | 3477 |
7 | Benq | 3468 |
8 | Radewoosh | 3462 |
9 | ecnerwala | 3451 |
10 | heuristica | 3431 |
# | User | Contrib. |
---|---|---|
1 | cry | 168 |
2 | -is-this-fft- | 162 |
3 | Dominater069 | 160 |
4 | Um_nik | 159 |
5 | atcoder_official | 156 |
6 | djm03178 | 153 |
6 | adamant | 153 |
8 | luogu_official | 149 |
9 | awoo | 147 |
10 | TheScrasse | 146 |
Suggestion pls...........
given , f(x)=2*(f(x-1)+g(x-1)-1)*(f(x-1)+g(x-1)-3)+12*f(x-1)-13 g(x)=(f(x-1)+g(x-1))*(f(x-1)+g(x-1)-4)+12*g(x-1)-7 here , f(0)=2,g(0)=1. if x is given how to find f(x) and g(x) when 1<=x<=10^18 and x is an non negative integer
Name |
---|